2013
DOI: 10.1136/annrheumdis-2013-eular.1378
|View full text |Cite
|
Sign up to set email alerts
|

FRI0251 Comparison of lipid profile including high molecular weight adiponectin (HMW-AN) after treatment with three different biologics in the patients with bio-naïve rheumatoid arthritis (RA)

Abstract: Background Three different mode of action of biologics (adalimumab, tocilizumab and abatacept) have been shown to provide clinical benefits in the patients (pts) who did not adequately respond to methotrexate (MTX-IR) in RA. In several studies including our report, moderate increase in cholesterol and HMW-AN, which is an anti-atherogenic adipocytokine, after treatment with TNF inhibitors has been reported1). However, there was no report in terms of comparison of effect of biologics on lipid profile. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There were no changes from baseline reported for TC [ 16 , 17 , 21 , 23 , 25 ] and TG [ 17 , 21 , 23 , 25 ]. Saito et al [ 24 ] reported increase in both HDL-C and LDL-C, but two other studies reported no significant change [ 17 , 21 , 23 , 25 ]. There was no significant effect on BP [ 17 ], atherogenic index [ 16 ], AIx [ 16 – 18 , 21 , 23 , 25 ], CAVI [ 18 ], cIMT [ 16 ], and carotid artery plaques [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were no changes from baseline reported for TC [ 16 , 17 , 21 , 23 , 25 ] and TG [ 17 , 21 , 23 , 25 ]. Saito et al [ 24 ] reported increase in both HDL-C and LDL-C, but two other studies reported no significant change [ 17 , 21 , 23 , 25 ]. There was no significant effect on BP [ 17 ], atherogenic index [ 16 ], AIx [ 16 – 18 , 21 , 23 , 25 ], CAVI [ 18 ], cIMT [ 16 ], and carotid artery plaques [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data on patients with RA treated with adalimumab were obtained from five RCTs (four full-length articles [ 26 29 ] and three conference abstracts [ 30 – 32 ]), five PC studies (four full-length articles [ 33 36 ] and one conference abstract [ 37 ]), and six RC studies (four full-length articles [ 38 41 ] and two conference abstracts [ 19 , 24 ]). There was no effect on TC [ 27 , 33 , 36 , 40 ] or TG [ 33 , 36 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessing factors that influence cardiovascular risk, studies have not reported changes in TC, triglycerides, LDL-C, or HDL-C levels for abatacept [ 169 , 217 ]. There is one study showing an increase in LDL-C [ 218 ], while there two showing improvements in HDL-C, both quantitatively and qualitatively [ 218 , 219 ]. No significant modification in cIMT [ 169 , 220 ] or BP [ 169 ] was observed, while BMI showed an upward trend; however, insulin sensitivity appeared to be improved [ 221 ].…”
Section: The Effects Of Biological Therapy On Cardiovascular Risk Fac...mentioning
confidence: 99%